Are Alcohol Tax Hikes Fully Passed Through to Prices? Evidence from Alaska - Kenkel, Donald S (American Economic Review, 2005)
On 1 October 2002, the State of Alaska increased taxes on malt beverages from $0.35 per gallon to $1.07 per gallon, increased taxes on wine from $0.85 per gallon to $2.50 per gallon, and increased taxes on distilled spirits from $5.60 per gallon to $12.80 per gallon. The net effect is that the tax on a standard serving rose from about 3 cents for beer, 2 cents for wine, and 4 cents for spirits to a uniform tax of 10 cents per standard serving of each type of alcohol beverage. This paper uses primary data on alcoholic beverage prices in Alaska to study a very basic question: What was the impact of the tax hikes on prices? An alcohol tax hike is often viewed as a public health policy tool to discourage excessive alcohol consumption and alcohol-related problems such as drunk driving. The impact of a tax hike on alcoholic beverage prices is a key link in the chain of the causality from the tax to public health. Economic theory and previous empirical studies, mainly of taxes on goods other than alcoholic beverages, do not provide very much guidance on what to expect following a tax hike. It is an empirical question. To answer the question, I conducted telephone surveys, just before and a year after the tax hike, of on-premise and off-premise alcohol retail establishments across Alaska.